Spin fluctuations in hydrogen-stabilized Laves phase UTi2H5. Issue 15 (3rd August 2019) - Buturlim, Volodymyr; Falkowski, Michał; Paukov, Mykhaylo; Koloskova, Oleksandra; Drozdenko, Daria; Dopita, Milan; Minárik, Peter; Mašková, Silvie; Doležal, Petr; Havela, Ladislav
ABSTRACT: Uranium Laves phase UTi2 does not exist in a pure form, but can be stabilised by the presence of hydrogen, which can be absorbed in concentration exceeding 5 H atoms/f.u. Low temperature specific heat, magnetic susceptibility, and resistivity indicate that UTi2 H5 is a spin fluctuator close to the verge of magnetic ordering. Its susceptibility follows at high temperatures the Curie–Weiss law with U effective moment µ eff[  =  3.1 µB /U and paramagnetic Curie temperature Θp   =  −200 K. The temperature dependence of specific heat exhibits a pronounced and weakly field dependent upturn in Cp / T versus T below 10 K reflecting the effect of spin fluctuations. It can be described by an additional T ½ term. The Sommerfeld coefficient γ   =  256 mJ/mol K 2 classifies the compound as a mid-weight heavy fermion. Spin fluctuations are affecting also electrical and thermal transport and thermoelectric power, which all resemble UAl2 . A lattice anomaly at ≈ 240 K, attributed to the melting of hydrogen sublattice, reflects in most of bulk properties.